Professional vocational master’s degree and as new educational technologies: a proposal for an online teaching and learning environment - Rosa, Marcelo Barcellos da (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
The professional master’s degree in Mineral Technology of the Federal University of Pampa, in partnership with the Federal University of Rio Grande do Sul and Federal University of Santa Maria was recommended by CAPES in mid-2012 and has its beginning scheduled for the first semester of 2013. In this paper, a proposal for a virtual media for teaching and learning for three disciplines, biogeochemical cycles, fundamentals of ecotoxicology and environmental control of water, using the Moodle platform aim to use the program as a model to be applicable to professors and master students, is presented. The characteristics semipresential of the course, as well as the heterogeneity of the students justify the application of alternative technologies in the consolidation of the course. Therefore, the proposal is presented as a diversified manner, as it provides a variety of various tools, including blogs, emails, forums, chat rooms, galleries, and daily updated materials (videos, texts) that contribute to the setting of modules worked in person. Thus, this proposal will allow an interaction between the users and the exposure of your opinion and contributing to the discussion and exchange of information, and provides both the possibility of learning asynchronously or synchronously, as well management time and location for the study, ie flexibility.